Pd-Based Nanoparticles as Catalysts for Improved Removal of Florfenicol Via Heterogeneous Fenton and Photo-Fenton(-Like) Processes - Casagrande-Denardin, J (American Chemical Society, 2023)
In this work, Fe2O3-Ni, Fe2O3-Ni-Pd, MgO-Ni, and MgO-Ni-Pd nanoparticles were synthesized, characterized, and used for the degradation of florfenicol (FLO). The main goals were to compare the removal capacity of Fe2O3-Ni and MgO-Ni nanocatalysts and evaluate the effect of Pd incorporation on Fe2O3-Ni and MgO-Ni nanoparticles on the degradation of FLO by heterogeneous Fenton(-like) and photo-Fenton(-like) processes. The adsorption and degradation processes of FLO were assessed, determining that the latter process is the principal mechanism for FLO degradation. Through the heterogeneous photo-Fenton process, the antibiotic was 78 and 44% removed using the Fe2O3-Ni and MgO-Ni nanocatalyst, respectively, improving degradation by 22% when Pd is incorporated into both nanostructures. FLO degradation occurs because of the generation of hydroxyl and superoxide radical and holes in the interface and the Fenton reaction with Fe and Mg present in the nanoparticles. Finally, the main organic intermediates produced during the degradation were identified, allowing the proposal of a degradation pathway. Thus, heterogeneous Fenton(-like) and photo-Fenton(-like) processes using nanoparticles as solid phase catalysts are an excellent alternative to FLO degradation from water, especially considering the easy recovery of the nanoparticles through a simple separation process such as filtration. © 2023 American Chemical Society.